1992
DOI: 10.1161/01.atv.12.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of synthetic class A amphipathic peptide analogues of exchangeable apolipoproteins in rats. Correlation with physical properties.

Abstract: Peptide analogues of the class A amphipathic helixes from exchangeable apolipoproteins mimic apolipoprotein (apo) A-I in a number of ways, including the ability to activate the enzyme lecithin: cholesterol acyltransferase, to associate with high density lipoproteins (HDLs), and to form HDL-like particles in the presence of lipids. This study investigated the metabolic properties of several of these peptide analogues in the rat Peptide analogues studied were 18A (referred to as L-18A to differentiate it from D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…Most of the radioactivity from both L-18A and D-18A was found in the liver and kidney. Because free 125 I did not appear in plasma or urine after injection of D-18A (in contrast to the case after injection of L-18A), it was concluded that D-18A remained in the tissues undegraded 3 days after injection (39). Thus, it is likely that in the case of peptides synthesized from all D-amino acids, some nondegraded peptide will remain in tissues for an undetermined prolonged period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the radioactivity from both L-18A and D-18A was found in the liver and kidney. Because free 125 I did not appear in plasma or urine after injection of D-18A (in contrast to the case after injection of L-18A), it was concluded that D-18A remained in the tissues undegraded 3 days after injection (39). Thus, it is likely that in the case of peptides synthesized from all D-amino acids, some nondegraded peptide will remain in tissues for an undetermined prolonged period.…”
Section: Discussionmentioning
confidence: 98%
“…Garber et al (39) reported on the tissue distribution and excretion of the peptide 18A. This peptide differs from 4F in that 18A does not have blocking groups as does 4F, and in 4F, two of the leucines on the hydrophobic face of the peptide have been changed to phenylalanines.…”
Section: Discussionmentioning
confidence: 99%
“…In some mice in the D4F IP group, the blood was collected 1 hour after D4F injection to determine D4F concentration by reverse-phase high-performance liquid chromatography as described previously. 25 Serum was stored at Ϫ80°C until analysis. Total cholesterol levels were measured with a commercially available kit (Sigma).…”
Section: Plasma Collection and Analytical Methodsmentioning
confidence: 99%
“…Arterial blood samples were collected after 1,5,10,20,30,45,60,120,180, and 240 min. The plasma concentration of 14 C-4F radioactive counts for each time point was measured and expressed as a percentage of counts present in the 1 min sample, as previously described ( 40 ). A similar procedure was used to measure the clearance of LPS from the circulation.…”
Section: C-4f and Bodipy-lps Plasma Clearance Studiesmentioning
confidence: 99%